Efforts, past and present, to stop the spread of a disease: a comparison of cholera and COVID-19 - Danyleyko, Andrew (My University, 2021)
Before scientific understanding was fully realized, the common belief about the causes of sickness were misunderstood and were often attributed to supernatural forces. Thanks to the efforts of doctors in London during the cholera outbreak in 1854, people now have a better understanding of what causes diseases, how they spread, and how that information can be used to save lives. This paper will show how Dr. Jon Snow’s contributions to epidemiology are just as relevant today regarding COVID-19 as they were when they were first proposed in 1854 for cholera.
Keywords: Jon Snow; epidemiology; cholera; COVID-19